ANALISIS MAKNA POLISEMI VERBA MIRU DALAM BAHASA JEPANG - Kasmawati kasmawati; Taqdir Taqdir (Universitas Diponegoro, 2024)
The purpose of this research is to analyze the polysemic meanings of the Japanese verb miru. This study examines the lexical and grammatical variations of miru, focusing on its meanings as described in the Daijirin dictionary and contextualized through examples in the Japanese novel Totto-chan, which has been translated directly into Indonesian. Using a qualitative approach, this research applies descriptive and interpretative analysis to explore how miru operates across different contexts and nuances within the novel. The findings reveal that miru encompasses a wide range of meanings, from visual perception to deeper conceptual and introspective senses, which are sometimes untranslatable without losing meaning in the source language. This research highlights the complexities of Japanese polysemy and contributes to a deeper understanding of linguistic nuances in Japanese, emphasizing the importance of context in translation and interpretation. <span lang=